Surgical Approach of Basal Cell Carcinoma on the Lower Eyelid: A Case Report - Gjyrdedi, Felisia; Qamo, Renis; Simaku, Ermal; Rrugeja, Irda (Journal of Ophthalmology and Research, 2024)
Basal cell carcinoma (BCC) is a common malignant tumor, originating from the basal cell layer of the epidermis. One of the known risk factors of BCC is intense exposure to ultraviolet radiation. The most common location is in the head and neck area, including the eyelids. More than 50% of BCCs of the eyelid initially occur on the lower lid. The gold standard of diagnosis of BCC is histopathology. Surgical excision using Mohs surgery is the first line of treatment for periocular BCC. Careful consideration should be made on reconstructing the eyelid after successful mass removal. Early diagnosis and treatment lead to a better functional and aesthetic outcome after surgery.